Strategi Pengelolaan Sumber Daya Manusia di Kepulauan Riau: Ditinjau Dari Aspek Pendidikan dan Ekonomi: English - Dio Samudra; Angga Ade Saputra (Jurnal Archipelago, 2025)
The Riau Islands as a strategic region with great maritime economic potential face challenges in managing quality human resources. This study aims to analyze human resource management strategies in the Riau Islands from educational and economic aspects in supporting sustainable development. Using a literature review method with qualitative descriptive analysis, this research examines various secondary sources including scientific journals, government reports, and official publications for the 2021-2025 period. Gap analysis shows the limited integration between the education system and the needs of the maritime industry and people's economy. The novelty of the research lies in identifying an integrated HRM management model that combines maritime vocational education approaches with digital economic development. The results show that effective HRM strategies require synergy between improving education quality, developing digital competencies, and optimizing maritime economic potential. Important findings indicate the need for educational curriculum transformation responsive to Industry 4.0 needs, strengthening institutional capacity of education, and developing a creative economy ecosystem based on local wisdom. The practical implications of this research provide policy recommendations for improving the Human Development Index of the Riau Islands through strategic investment in quality education and sustainable economic development centered on society